-18=5-3(6t+5)

Simple and best practice solution for -18=5-3(6t+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18=5-3(6t+5) equation:


Simplifying
-18 = 5 + -3(6t + 5)

Reorder the terms:
-18 = 5 + -3(5 + 6t)
-18 = 5 + (5 * -3 + 6t * -3)
-18 = 5 + (-15 + -18t)

Combine like terms: 5 + -15 = -10
-18 = -10 + -18t

Solving
-18 = -10 + -18t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '18t' to each side of the equation.
-18 + 18t = -10 + -18t + 18t

Combine like terms: -18t + 18t = 0
-18 + 18t = -10 + 0
-18 + 18t = -10

Add '18' to each side of the equation.
-18 + 18 + 18t = -10 + 18

Combine like terms: -18 + 18 = 0
0 + 18t = -10 + 18
18t = -10 + 18

Combine like terms: -10 + 18 = 8
18t = 8

Divide each side by '18'.
t = 0.4444444444

Simplifying
t = 0.4444444444

See similar equations:

| T-6y-2y=40 | | 15x+6=72+10x | | n-5(3)=36 | | 8v+22=6(v+7) | | 11x^2-8x-3=0 | | 26-8z=2z+16 | | 3y+13.6=40 | | 4u+-2=-6u+28 | | 3n-5=36 | | 8v+22=6(v+1) | | 15p^6-64n^3-10p^2=0 | | 4=e^6x | | 14+12=-5x+2x | | 12=-3(-2)-4y | | 5-2[x-4]=-11 | | -8v-22=6(v+1) | | 10-(-1x)=17x+2 | | x=-1.75+(.5-.125x) | | -2x+-2=2x-2 | | p-8=-9+p | | 20v^2+11v-3=0 | | 4x-4=5x-5+3x+6 | | 5a+30=6a+16 | | 2x+12+5x-9+6x-2=180 | | 13-(2c+2)=2c(c+2)+3c | | 216=8(5a+71) | | 9x-10y=-1 | | 5(x+2)=8x+1 | | 4x^4+10x^3y-6x^2y^2=0 | | log(2)(7x+6)=3 | | (2x-5y)-(x+y)= | | 6x+4=6x-3 |

Equations solver categories